The Perception of Health and the Change in Nutritional Habits of Healthcare Professionals During the COVID-19 Pandemic - Doğan, Yağmur Nil; Dogan, Ilkay; Kılıç, İbrahim (Progress in Nutrition, 2021)
Study Objectives: The COVID-19 pandemic and the quarantine process affected people’s normal lives, nutritional types and habits, activities, and psychological/mental states. Due to the COVID-19 pandemic and restriction decisions, healthcare professionals’ workload and working hours have increased. To determine the change in the nutritional habits of healthcare professionals who play the most important role in the COVID-19 pandemic process and their perception of health. Methods: Doctors (specialists or practitioners n=193), nurses/midwives (n=147), medical secretaries and paramedics (n=63) working in state hospitals, university hospitals, family medicine centers, or private hospitals before and during the COVID-19 pandemic were included in the study. The perception of health scale and a questionnaire were applied to a totally of 403 participants. Comparisons among the changes in the nutritional habits of healthcare professionals before and during the COVID-19 pandemic were performed using the paired t test for continuous variables, McNemar-Bowker’s test for categorical variables. Results: It was observed an increase in the working hours in a day of healthcare professionals. The frequency of having breakfast, having lunch, having dinner, and having snacks had decreased. An increase in the consumption of foods that boost the immune system has been observed. While healthcare professionals had unbalanced nutrition, they were aware of the importance of adequate nutrition. Conclusions: By reaching the number of healthcare professionals who can work adequately and effectively, the working hours of healthcare professionals can be reduced in the pandemic.